Changes in consumer behaviour caused by the Coronavirus (COVID-19): evidence from Portugal - Fragata, Anabela (Archives of Business Research, 2020)
This study attempts to explore Portuguese consumers sentiments and concerns during the coronavirus pandemic, the degree of trust in the recovery of the economy, month income affected by the pandemic, changes in online shopping behaviour, the consumer buying intentions for some products/services categories during the lockdown. We also analysed consumer concerns with food waste, or more sustainable product buying choices, brand loyalty and tourism issues impact like cancelled flights or accommodation and plans to schedule vacation away from home in 2020. Further, the study focuses on the change in the media consumption habits i.e., types and usage of media since the COVID-19 outbreak and also the various ways in which they are using social media to stay connected, informed, and entertained.